Advocate for the COVID-19 Vaccine for Pregnant and Breastfeeding Women. Issue 3 (May 2021) - Spatz, Diane L.
Abstract : Many professional organizations and agencies have advocated for pregnant women and breastfeeding women to be offered the COVID-19 vaccine. Our breastfeeding expert, Dr. Spatz, reviews their recommendations and ways nurses can advocate for this population to receive the vaccine.